Information Quality and Compatibility as Determinants of M-Wallet Usage in Indonesia. - Prakarsa, Graha; Nursyanti, Reni; Putra, Prayuda Mulyadi; Saputra, Renda Sandi (iora, 2025)
This study aims to assess the acceptance of mobile wallet applications in Indonesia by incorporating Information Quality and Compatibility as external factors within the framework of the Technology Acceptance Model (TAM). A quantitative approach was employed, and data from 208 respondents were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings indicate that both Information Quality and Compatibility have a positive and significant influence on Perceived Usefulness and Perceived Ease of Use. Furthermore, these two variables also significantly affect Continuance Intention to Use, which subsequently impacts the Actual Use of mobile wallets. Overall, Information Quality and Compatibility contribute 56% to Perceived Usefulness, 52.4% to Perceived Ease of Use, and 43.8% to Continuance Intention to Use. These findings offer valuable insights for application developers seeking to enhance mobile wallet adoption in Indonesia.